A Judeo-Christian account of human dignity in Canadian law and public policy - Penninga, Mark; University of Lethbridge. Faculty of Arts and Science (Lethbridge, Alta. : University of Lethbridge, Faculty of Arts and Science, 2008, 2008)
Understanding human dignity is integral to protecting human rights. An examination of Canada‘s Supreme Court decisions and Canadian public policy debates reveals that human dignity is being defined synonymously with individual autonomy and equality. This narrow understanding has serious implications for people who are not able to assert their autonomy. To understand the philosophical ideas behind these decisions, this thesis examines classical, modern, and postmodern accounts of human dignity and concludes that they fall short in providing an objective grounding for dignity that is truly human. It then looks to the Judeo- Christian account of human dignity to provide a transcendent foundation for human dignity. With this account, persons are rational and physical, relational, inviolable, and teleological – a hopeful contrast to the prevailing contemporary accounts. This thesis then defends the place of this religious perspective in our secular country.
vi, 182 leaves : ill. ; 29 cm.
Keywords: Dissertations, Academic; Dignity -- Political aspects -- Canada; Dignity -- Religious aspects -- Christianity; Human rights -- Political aspects -- Canada; Human rights -- Religious aspects -- Christianity; Respect for persons -- Law and legislation -- Canada